Examination of relationships among trait-like individual differences, state-like individual differences, and learning performance. - Chen, Gilad; Gully, Stanley M.; Whiteman, Jon-Andrew; Kilcullen, Robert N. (Journal of Applied Psychology, 2000)
Several authors (e.g., J.T. Austin & H.J. Klein, 1996; R. Kanfer, 1990b, 1992) have urged researchers to examine comprehensive models of distal individual differences as predictors of proximal motivational processes and performance. Two field studies in an academic setting tested a model of relationships among trait-like individual differences (cognitive ability, general self-efficacy, and goal orientation), state-like individual differences (state anxiety, task-specific self-efficacy, and goals), and learning performance. Most hypothesized relationships among these constructs received support when tested on 2 samples, when examining different performance episodes, and when using different goal orientation and state-anxiety measures. In general, state-like individual differences were found to mediate the relationships between trait-like individual differences and learning performance. Implications of these results are discussed and suggestions for future research are provided.